Pengaruh Pengungkapan Tanggung Jawab Sosial Perusahaan Terhadap Kinerja Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang tercatat di Bursa Efek Indonesia pada Tahun 2006 sampai dengan 2008) - Umi Sulistiyanti (Jurnal Aplikasi Bisnis, 2016)
This research was aimed to examine the influence of corporate social responsibility disclosure to company performance. Corporate social responsibility disclosure needs to be done as a form of communicating the social and environmental impacts of the economic activity of the organization's special interest group, to society as a whole. The sample used was 10 Manufacturing Companies listed on BEI that done CSR disclosure in their annual reports for three years (Year 2006 to 2008). This study concluded that: (I) Testing simultaneously found a significant influence on the disclosure of corporate social responsibility to the ROA, ROE, but had no effect on CAR. (2) The influence of corporate social responsibility disclosure to the CAR through ROE as a intervening variable, but had no effect on ROA as intervening variables.